Segurança na Internet das Coisas: Varredura, Análise e Estatística de Redes sem Fio em Bom Jesus do Itabapoana - Alves, Ana Julia; de Souza, Wesley Folly Volotão (Anais do Encontro Nacional de Computação dos Institutos Federais (ENCompIF), 2020)
In this work we will do a research with the aid of the wardriving method so that we can find out how much Wi-Fi networks in our region are vulnerable to attacks. To this end, we will capture and analyze data such as: security protocols, wps configurations, and preferred networks.